Les techno-complexes Ibéromaurusiens d’Ifri El Baroud (Rif Oriental, Maroc) - Nami, Mustapha (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
This report summarizes the results of excavations conducted by the Institut National des Sciences de l’Archéologie et du Patrimoine and the German Archaeological Institute at Ifri el-Baroud (Gunpowder Cave). The cultural deposits of Ifri el-Baroud showed to be of a depth of up to 3 meters and to have formed between the 19th and 8th century BC, as proved by a series of radiocarbon datings. The upper part of the stratigraphy consists of an “escargotière” from terrestrian snails, the lower part is formed by a compact and fi ne sediment. The stone industry shows a development from bigger artifacts to the typical lithic assemblage of the Iberomaurusien (especially backed blades) and to microlithic forms. Excavations at Ifri el-Baroud complement others undertaken by the same project at Ifri n’Ammar (upper deposits) and Hassi Ouenzga Plein Air. The article will be available as a PDF in the near future.